Forage Potential of Cowpea (Vigna Unguiculata L. Walp) - Ayan, I.; Mut, H.; Başaran, U.; Acar, Z.; Önal-Aşci, O.O. (Soc Field Crop Sci, 2012)
Nine Cowpea (Vigna unguiculata L. Walp) genotypes were assessed for forage yield and quality features during 2005 and 2006 summer growing season at two locations (Samsun and Kavak) in Turkey. Experiments were established on May and arranged in a randomized complete block design with 3 replications in both years and locations. Although cowpea is not grown for forage purposes, their forage yield and quality are desirable in experiment conditions. Forage yield significantly (P<0.01) affected by genotype, year and location and ranged between 6.03 and 7.94 t ha-1 among genotypes over the years and locations. No differences were found in crude protein (CP) among cultivars and years, which ranged from 170.2 g kg-1 for cultivar Akkiz up to185.2 g kg-1 for genotypes G3, G4 over the years and locations. There were no significant differences among genotypes for ADF, NDF, Mg and P contents. P, Mg, Ca and K contents in all the genotypes were higher than animal needs in both locations. In general, cowpea genotypes had higher forage yield, CP and lower ADF and NDF at Samsun compare to Kavak location.
Keywords: Adf; Cowpea; Forage Yield; Mineral Mater; NDF; Protein; Turkey